(untitled) (Iter, 2022)
In the next assignment we will realized some approaches about the rol politician that the Constantinople’s senate occupied inside of the institutional scaffolding of the Eastern roman empire. About o f little reconstruction o f the origin of the institute senatorial, where we will analyzed the social composition o f the members of the same, we will focus our attention in the XI century. Traditionally considered this century like a “not turning point” for the structural framework of the Eastern empire, view the simultaneous crisis o f a political, military and economic nature that transited their respective subsystems, we will pretend highlight how the Senate was becoming in a space o f power that really could come to exercise a truly “institutional pressure”. However, our analysis c o u ld n ’t escape in comparative perspective another institutes that they exercised like “interested groups”:the imperial Army and the Patriarchy of Constantinople.